Seed Banks in Urban Vacant Lots of a Latin American Megacity Are Easily Germinable and Strongly Dominated by Exotic Flora - Castro-Morales, S (Springer, 2020)
Seed banks in the soil play a role in the temporal continuity and succession of vegetation in urban vacant lots. Therefore, it is necessary to know the composition, abundance and dynamics of the seeds stored in the lots’ soils to understand their effect on spontaneously established urban plants. We hypothesized that soil seed banks in the urban vacant lots of Santiago, Chile, have a high abundance of seeds and an easily germinable bank of mainly exotic annual weeds. Additionally, 5 drivers (lot age, lot area, distance to urban centre, distance to urban boundary, and population density) were associated with the density of seed banks in the soil of urban lots. In 20 lots studied, 18 soil samples (150 cm3 per sample) were collected, 9 samples at a depth of 0–5 cm, and 9 samples at >5–10 cm. This seed bank was studied by seed germination in each of the soil samples. Thirty-eight species recorded in the seed banks were exotic (83.7% were European, Mediterranean or Eurasian) and only three native. Two species could be identified up to genus only. We recorded in total 2934 seedlings in the upper soil layer and 506 seedlings in the lower soil layer from the 20 lots analyzed. The species frequency in the upper seed bank was positively and significantly correlated with the frequency of the lower seed bank and with species frequency for above-ground vegetation. In the upper soil layer, our results showed that smaller lots located in the most densely populated neighborhoods contain more weed seed density in the soil than greater lots located in less densely populated areas. The rest of the factors evaluated were not associated with the density of the seed banks in the soil. The results indicate that research in seed banks in urban habitats should be expanded and deepened, since the seed banks are determinants in the spatio-temporal abundance and diversity of above-ground spontaneous urban lot flora. © 2020, Springer Science+Business Media, LLC, part of Springer Nature.
Keywords: Abandoned area; Exotic plant; Seed bank; Urban flora; Urban vegetation; Urban weed